Oxidative-stress-mediated apoptosis triggered by microplastics disrupts bovine oocyte maturation - Yu Wang; Jiaming Yue; Yijing Yin; Yan Zhang; Yi Zheng; Hao Jiang; Jiabao Zhang; Bao Yuan; Liang Shuang (Theriogenology, 2026)

Constant-voltage triboelectric nanogenerator coupled with an intermittent speed-up mechanism and bionic jellyfish blades for low-speed water flow energy harvesting - Chenxi Li; Yongle Zhou; Fupu Xie; Jiaming Zhang; Yi Li; Hongwei Wang; Kaisheng Li; Zihao Li; Siyuan Liu; Tianyu Li (Chemical Engineering Journal, 2026)

Mitigation of antibiotic resistance risk in aerobic sludge by zero-valent iron: From pathogen reduction to conjugation inhibition and network weakening - Ying Wu; Lin Zhu; Guoping Lin; Xuezhu Han; Jingpeng Li; Jiaming Yi; Dan Huang; Meizhen Wang (Bioresource Technology, 2026)

Machine learning prediction and interpretability of sewage sludge pyrolysis gas yield and composition - Yi Xiao; Jingyi Li; Qigui Niu; Tianxue Yang; Jiaming Zhao; Xiaowei Wang; Dongyang Li (Journal of Environmental Chemical Engineering, 2026)

Longitudinal association between metal mixture exposure and non-alcoholic fatty liver disease: A prospective cohort study based on generative adversarial networks - Jiaming Fu; Jinhao Jia; Honghui Li; Guojie Qiao; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; Xiaoyu Li; et al. (Environmental Pollution, 2026)

Adaptive NN finite-time inverse optimized formation fault-tolerant control for multi-USV systems with actuator faults - Jiaming Zhang; Yi Zuo; Shaocheng Tong (Ocean Engineering, 2026)

Nanoconfined humic acid-supported nZVI enhances imidacloprid remediation without compromising soil microbiome or exacerbating ARG health risks - Na Li; Jiaming Yi; Lin Zhu; Du Chen; Meizhen Wang; Dan Huang (Environmental Research, 2026)

Electronic structure modulation in Co-doped NiFe-LDH for efficient ethylene glycol oxidation in simulated seawater - Jiaming Ding; Tao Li; Yi Ma; Huan Ge; Ning Jian; Jialing Tang; Jing Yu; Jordi Arbiol; Haiting Wang; Luming Li; Andreu Cabot; Junshan Li (Chemical Engineering Journal, 2026)

Coordinated nitrogen placement and rate optimization strengthen root–nitrogen coupling and improve nitrogen use efficiency in dryland maize - Fu Liu; Xiaoyu Ning; Jiaming Yang; Zijun Han; Yunfei Ren; Jinxia Wang; Haibo Hu; Yi Zhou; Xiaogang Yin; Shikun Sun; Juan Han; Yuncheng Liao; et al. (Soil and Tillage Research, 2026)

Revealing the antioxidant potential of Artemisia integrifolia L.: Integrated discovery of bioactive compounds via UHPLC-DPPH and activation of the Nrf2/HO-1 signaling pathway - Huimin Li; Qian Gao; Yijin Wu; Jingya Ruan; Jiaming Cheng; Yi Zhang; Tao Wang (Phytochemistry, 2026)

Unraveling the adverse outcome pathways of metabolic dysfunction-associated steatotic liver disease triggered by environmental mixtures via biological knowledge-driven machine learning - Jiaming Fu; Guojie Qiao; Kerong Ma; Jinhao Jia; Honghui Li; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; et al. (Journal of Hazardous Materials, 2026)

Effects of microenvironmental factors on water-insoluble precipitation induced by soybean urease - Chongda Duan; Jiaming Zhang; Yi Luo; Yanzi Sun; Jiaxing Liu; Xiang Lv (Journal of Environmental Chemical Engineering, 2026)

Components with potential anti-inflammatory effect from the seeds of Dolichos lablab - Wei Zhang; Yijin Wu; Jiaming Cheng; Jingya Ruan; Yingying Wang; Lequan Yu; Dan Wang; Yi Zhang; Tao Wang (Journal of Natural Medicines, 2026)

P300-mediated H3K56la delactylation promotes copper-induced steroidogenesis disorders in human ovarian granulosa cells - Panlin Wang; Jiaming Xiao; Bingbing Wang; Yi Zhang; Ke Xu; Yingjie Dou; Qianqian Guo; Ye He; Yan Sun; Wenxiang Wang (Journal of Hazardous Materials, 2026)

A novel multifunctional bacterial consortium synergistically promotes rhizoremediation of dibutyl phthalate and cucumber growth: Insights from multi-omics analyses - Jiaming Xu; Yan Li; Haoyan Han; Yi Wu; Yue Tao; Yuexuan Ma; Zhao Jiang; Ying Zhang (Journal of Environmental Sciences, 2026)

In-situ sulfur element-induced heterogeneous interface engineering for high-performance supercapacitors - Mingzhe Shan; Yi Jiang; Ruixiang Xu; Bin Cai; Yi Gao; Heju Zhao; Jiaming Wang; Yaozeng Lu; Xiqing Song; Surong Tan; Yishan Yuan; Zining Li; et al. (Chemical Engineering Journal, 2026)

GIS-based Geotourism Route Design in Changbaishan Global Geopark - Junbo Zhao; Jinxin He; Jian Yi; Xiangjin Ran; Jiaming Li (Geoheritage, 2026)

Tracking 3D desiccation crack evolution and permeability dynamics in expansive soil - Yun Peng; Jiaming Zhang; Yi Luo; Tianle Liu; Mingjian Hu; Shuai Liu (Bulletin of Engineering Geology and the Environment, 2026)

Morphology–aware spatiotemporal prediction of cumulonimbus–related radar echoes using CSDP–Net - Deyi Wang; Xu Wang; Zhenhong Cheng; Xin Chang; Hongping Yuan; Jixiang Yang; Yi Liang; Jiaming Hu; Ting Zhang (Theoretical and Applied Climatology, 2026)

Development of an indirect ELISA and an immunochromatographic test method for early detection of Haemonchus contortus infection in sheep - Xueqiu Chen; Lingyun Mou; Manqin Deng; Jingju Zhang; Jiaming Yu; Jianfang Li; Hongli Zhang; Guangxu Ma; Yi Yang; Aifang Du (Veterinary Parasitology, 2026)

Model-based assessment of impacts of aeration intensity on the water-energy-carbon nexus of a full-scale wastewater treatment plant - Xinhong Han; Lu-Man Jiang; Lifeng Lin; Long Wang; Peng Peng; Jiaming Hu; Jiguang Ying; Yi Yang; Rui Tang; Zhen Zhou (Journal of Environmental Management, 2026)

Structural properties of two glycans in the fruits of jujube and their regulation effect of M1-type and M2-type macrophage - Jingya Ruan; Ping Zhang; Jiaming Cheng; Lequan Yu; Yijin Wu; Yinuo Zheng; Yi Zhang; Tao Wang (Carbohydrate Polymers, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Anti-inflammatory metabolites from the leaves of Ohwia caudata - Qianqian Zhang; Ping Zhang; Yijin Wu; Huimin Li; Jingya Ruan; Jiaming Cheng; Yi Zhang; Tao Wang (Phytochemistry, 2026)

Metformin drives the antibiotic resistome in activated sludge by reshaping microbial communities and promoting horizontal gene transfer - Jiaming Yi; Zhengtao Li; Xuezhu Han; Jingpeng Li; Haotian Liu; Lin Zhu; Meizhen Wang (Journal of Hazardous Materials, 2026)

Emerging evidence of nighttime mercury oxidation driven by nitrate radical-activated heterogeneous halogen chemistry - Yan Wang; Zhenya Duan; Yi Tang; Shuxiao Wang; Zhijian Li; Qin Wang; Jiaming Fu; Qingru Wu (Journal of Hazardous Materials, 2026)

Development of a modified CaCl2·6H2O shape-stabilized composite phase change material for the greenhouse soil-cooling system - Fuyu Qin; Runhua He; Lingzhi Zhong; Tao Xu; Jiaming Gao; Ximin Lin; Yi Yang; Weitao Shao (Energy and Buildings, 2026)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Research on the dynamic properties of rubber-recycled brick-coarse aggregate concrete through pore structure evolution - Shucheng Yuan; Jiayu Zeng; Jiaming Mai; Siwei Du; Yanjindong Yi; Kunpeng Li; Wei Liang (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

A normalized small waterbody size transition index for remote sensing drought monitoring - Xi Wang; Wen Zhang; Junjie Li; Zhe Wang; Zhen Zhang; Hui Wang; Yanjiao Song; Jiaming Chen; Yi Bao; Bingsun Chen; Qianyu Wang; Jia Chen; et al. (Journal of Hydrology, 2025)

Adipose-derived soluble fractions activated bioink promotes cutaneous repair and regeneration via mobilizing endogenous reparative cells - Wei Zhang; Jiaming Shao; Hanlei Zhou; Min Yang; Chenghao Cai; Fang He; Yiran Wang; Pengqin Xu; Sizhan Xia; Tingting Weng; Jialiang Wang; Ronghua Jin; et al. (Chemical Engineering Journal, 2025)

Recycling waste poly(ethylene terephthalate) to prepare a Zn–MOF and its application as a nucleating agent for plastics and antibacterial agent on cotton fabrics - Xiaohui Lin; Jiaming Xu; Guoliang Sun; Jingjing Sun; Yi Xiao; Yanling Hu; Jinqing Yang; Yubiao Liao; Jianchun Liu; Mingyi Shang; Kun Wu (Journal of Environmental Chemical Engineering, 2025)

Impact of dynamic desiccation cracks on hydrological processes and stability in expansive clay slopes: A coupled dual-permeability modeling approach - Yi Luo; Jiaming Zhang; Chao-Sheng Tang; Guosheng Jiang; Thom Bogaard (Engineering Geology, 2025)

Exploring the effects of weather-driven dynamics of desiccation cracks on hydrological process of expansive clay slope: Insights from physical model test - Yi Luo; Xinyu Hou; Jiaming Zhang; Yujie Wang; Mingjian Hu; Guosheng Jiang; Chao-Sheng Tang (Journal of Hydrology, 2025)

Water quality prediction at large-Scale: Systematic assessment of decomposition-deep learning models - Jiahui Shi; Lixiao Ni; Jiaming Liu; Hui Chen; Yushen Ma; Yi Zhang; Qingwei Lin; Zhen Zhang; Hang Xu; Yiping Li (Journal of Cleaner Production, 2025)

The comparison of anticrystallization effects of cellulose derivatives with polyvinylpyrrolidone and poloxamer on andrographolide: In vitro and in vivo characterization - Xiaoyi Zhang; Peixia Luo; Jiaming Wang; Lei Yang; Zipei Pang; Shufeng Chen; Yi Zhou; Linghao Qin (Carbohydrate Polymers, 2025)

Evaluation of Geosites in Changbaishan Global Geopark based on Fuzzy AHP and TOPSIS - Jiaming Li; Jinxin He; Peng Lu; Xiangjin Ran; Jian Yi (Geoheritage, 2025)

Anthracnose caused by Colletotrichum siamense on rambutan in China - Gengxin Chen; Jinhua Sun; Jiaming Cui; Yu Wang; Yajun Ran; Deqiang Gong; Yi Yang; Meijiao Hu; Min Li (Crop Protection, 2025)

Associations of wildfire-derived particulate matter with hospitalization, emergency department visits and mortality: A systematic review and meta-analysis - Yiyi Wang; Jie Chen; Yujia Huang; Jiaming Wang; Yi Xiong; Tao Xue; Xu Yue; Fuping Qian; Meng Wang (Environmental Research, 2025)

Characterization and risk-quantification of antibiotic resistome in grain-based and non-grain cropping soils - Jingpeng Li; Lin Zhu; Xiaodi Li; Xuezhu Han; Jiaming Yi; Ying Wu; Meizhen Wang (Environmental Pollution, 2025)

Analytical Model of Passive Heave Compensator Considering Gas Exchange Between Accumulator and Gas Bottles - Yong Zhan; Mengxuan Hou; Yuzhi Yao; Jiaming Jia; Bailin Yi; Dongyue Qu (Journal of Marine Science and Engineering, 2025)
Dynamic response characteristics of the passive heave compensator with auxiliary gas bottles are investigated in this paper. A mathematical model of the passive heave compensator is developed which includes mechanics, hydraulics and pneumatics. The key innovation of the proposed model is that the thermodynamic model of gas exchange between the piston accumulator and the gas bottles is derived and discussed. Meanwhile, a one-dimensional model of the pipeline resistance effect is established to calculate the pressure drop across the oil pipeline. The proposed model is used to evaluate the different design parameters of the passive heave compensator for heavy lifting cranes. A study was conducted to investigate the influence of the design parameters on the effectiveness of the passive compensator to reduce the payload displacement. The simulation results indicated that substantial improvement may be possible by careful design parameter selection and optimization.

Cement-MgO synergetic stabilized earth-straw mix: From material performance to building simulation - Jiaming Cui; Junjie Li; Yi Du; Guillaume Habert (Energy and Buildings, 2025)

Optimization of fiber orientation and topology for curved-folded laminated bamboo veneer shells - Xianchuan Meng; Yi Min Xie; Jiaming Ma (Engineering Structures, 2024)

Innovative approach to enhancing phosphogypsum mechanical properties and stabilizing/solidifying contaminants - Lina Xiao; Jiaming Zhang; Yi Luo; Xiaojian Qi; Javid Hussain; Guosheng Jiang (Sustainable Chemistry and Pharmacy, 2024)

A novel sunflower-like nanocarrier based on dual milk-derived proteins for improved bio-accessibility, stability and antioxidant activity of anthocyanin - Shuangshuang Wang; Yi Ding; Liqing Xu; Jiaming Li; Minghui Zhang; Qisheng Hu; Haiyan Wang; Jiaying Zhang; Lili Zhao; Jing Zhang; Wupeng Ge (Food Hydrocolloids, 2024)

The involvement of tumor necrosis factor receptor-associated factor 6 in regulating immune response by NF-κB at pre-molt stage of Chinese mitten crab (Eriocheir sinensis) - Jialin Li; Yuhan Ma; Zihao Wu; Jiaming Li; Fengchi Wang; Zhichao Yang; Yuting Xi; Dazuo Yang; Yusheng Jiang; Qilin Yi; Shu Huang (Fish & Shellfish Immunology, 2024)

Effects of dry-wet cycles on the mechanical properties of sandstone with unloading-induced damage - Gan Nan; Jiaming Zhang; Yi Luo; Xinlong Wang; Zhongyi Hu (Journal of Mountain Science, 2024)

Effects of improper emergency mitigations on a large-scale landslide triggered by road excavation: A case study of the Fengping landslide, Hubei province, China - Yi Luo; Jiaming Zhang; Zhi Zhou; Guosheng Jiang; Modong Duan (Bulletin of Engineering Geology and the Environment, 2024)

Clustering and optimization of nodes, beams and panels for cost-effective fabrication of free-form surfaces - Minghao Bi; Yuanpeng Liu; Tao Xu; Yunzhen He; Jiaming Ma; Zicheng Zhuang; Yi Min Xie (Engineering Structures, 2024)

An intelligent control method for PEMFC air supply subsystem to optimize dynamic response performance - Qingqing Su; Jiaming Zhou; Fengyan Yi; Donghai Hu; Dagang Lu; Guangping Wu; Caizhi Zhang; Bo Deng; Deming Cao (Fuel, 2024)

Design optimisation of structures made of a small number of prescribed building blocks - Hongjia Lu; Ting-Uei Lee; Jiaming Ma; Yi Min Xie (Engineering Structures, 2024)

Thermal inactivation kinetics of Listeria monocytogenes in milk under isothermal and dynamic conditions - Xiang Wang; Jiaming Zheng; Linyin Luo; Yi Hong; Xiaofeng Li; Yuqi Zhu; Yufan Wu; Li Bai (Food Research International, 2024)

Molecular Determinants of Neurocognitive Deficits in Glioma: Based on 2021 WHO Classification - Kun Zhang; Tianrui Yang; Yu Xia; Xiaopeng Guo; Wenlin Chen; Lijun Wang; Junlin Li; Jiaming Wu; Zhiyuan Xiao; Xin Zhang; Wenwen Jiang; Dongrui Xu; et al. (Journal of Molecular Neuroscience, 2024)
Cognitive impairment is a common feature among patients with diffuse glioma. The objective of the study is to investigate the relationship between preoperative cognitive function and clinical as well as molecular factors, firstly based on the new 2021 World Health Organization’s updated classification of central nervous system tumors. A total of 110 diffuse glioma patients enrolled underwent preoperative cognitive assessments using the Mini-Mental State Examination and Montreal Cognitive Assessment. Clinical information was collected from medical records, and gene sequencing was performed to analyze the 18 most influenced genes. The differences in cognitive function between patients with and without glioblastoma were compared under both the 2016 and 2021 WHO classification of tumors of the central nervous system to assess their effect of differentiation on cognition. The study found that age, tumor location, and glioblastoma had significant differences in cognitive function. Several genetic alterations were significantly correlated with cognition. Especially, IDH , CIC , and ATRX are positively correlated with several cognitive domains, while most other genes are negatively correlated. For most focused genes, patients with a low number of genetic alterations tended to have better cognitive function. Our study suggested that, in addition to clinical characteristics such as age, histological type, and tumor location, molecular characteristics play a crucial role in cognitive function. Further research into the mechanisms by which tumors affect brain function is expected to enhance the quality of life for glioma patients. This study highlights the importance of considering both clinical and molecular factors in the management of glioma patients to improve cognitive outcomes.

An experimental study of mitigating coastal dune erosion by using bio-carbonization of reactive magnesia cement - Jiaming Zhang; Yuhao Li; Yi Luo; Yanjun Li; Qinggang Yang; Zijian Shen (Marine Georesources & Geotechnology, 2024)

Thermal-and-mechanochemical recycling of waste polypropylene into maleated-epoxided degradation products as warm-mix asphalt modifier: Performance improvement and production mechanism analysis - Xiong Xu; Yaming Chu; Yi Luo; Yuhao Peng; Nannan Yang; Jiaming Yan; Xuyong Chen; Fuliao Zou; Anand Sreeram (Journal of Cleaner Production, 2023)

Fibrillation of whey protein isolate by radio frequency heating for process efficiency: Assembly behavior, structural characteristics, and in-vitro digestion - Shuangshuang Wang; Yuxia Xie; Yi Ding; Zhenquan Huo; Jiaming Li; Jiaqing Song; Yucui Huo; Lili Zhao; Jing Zhang; Shaojin Wang; Jiaying Zhang; Wupeng Ge (Innovative Food Science & Emerging Technologies, 2023)

Study on calcareous sand treated by MICP in different NaCl concentrations - Jitong Zhao; Yi Shan; Huawei Tong; Jie Yuan; Jiaming Liu (European Journal of Environmental and Civil Engineering, 2023)

FOXO-like Gene Is Involved in the Regulation of 20E Pathway through mTOR in Eriocheir sinensis - Jiaming Li; Yuhan Ma; Zhichao Yang; Fengchi Wang; Jialin Li; Yusheng Jiang; Dazuo Yang; Qilin Yi; Shu Huang (Journal of Marine Science and Engineering, 2023)
The Forkhead Box O (FOXO) gene plays a key role in various biological processes, such as growth, metabolism, development, immunity and longevity. Molting is an essential process for crustacean growth, which is mainly regulated by 20-hydroxyecdysone (20E) and molt-inhibiting hormone (MIH). Although the role of FOXO in regulating the immune response of crustaceans is well documented, its involvement in controlling crustacean molting remains unclear. In this study, a FOXO-like gene (designed as EsFOXO-like) was identified in Eriocheir sinensis, and the regulation of the 20E pathway by EsFOXO-like was also investigated. The coding sequence of EsFOXO-like was 852 bp, which consisted of 283 amino acids including a conserved Forkhead (FH) domain. EsFOXO-like shared high similarity with FOXO genes from other crustaceans, and the mRNA expression levels of the EsFOXO-like gene were highest in the hepatopancreas and lowest in the hemocytes. However, transcription and protein expression of the EsFOXO-like gene were found to be up-regulated only during the pre-molt stage in the hepatopancreas, with lower expression levels observed at the post-molt stage. To explore the role of EsFOXO-like in the 20E pathway, EsFOXO-like was firstly inhibited by a specific FOXO inhibitor (AS1842856) and then through an EsFOXO-like dsRNA injection, respectively, and the results showed that the relative expression levels of EsFOXO-like were notably decreased in the hepatopancreas after both the inhibitor and dsRNA treatments. The 20E concentration, the mRNA expression levels of the 20E receptors including the ecdysone receptor (EcR) and the retinoid-X receptor (RXR) and EsmTOR transcription in the AS1842856 group or the EsFOXO-RNAi group were all significantly higher than that in the control group, while the mRNA expression level of EsMIH was significantly decreased after EsFOXO-like inhibition. To further investigate whether the EsFOXO-like acts through mTOR or not, Rapamycin was administered to inhibit mTOR activity in EsFOXO-like inhibited crabs. The results revealed a significant reduction in the concentration of 20E and the expression level of EsMIH in the AS1842856 + Rapamycin group compared to the AS1842856 + DMSO group, accompanied by an increase in EsEcR and EsRXR expression. These findings collectively suggest that EsFOXO-like regulates the 20E pathway through mTOR, which offered valuable insights into the understanding of the molting process in crustaceans.

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Topology optimization of ribbed slabs and shells - Jiaming Ma; Yunzhen He; Zi-Long Zhao; Yi Min Xie (Engineering Structures, 2023)

Brain microstructural alterations in the left precuneus mediate the association between KIBRA polymorphism and working memory in healthy adults: a diffusion kurtosis imaging study - Junxia Wang; Sichu Wu; Yi Sun; Jiaming Lu; Jilei Zhang; Yu Fang; Zhao Qing; Xue Liang; Wen Zhang; Qian Chen; Xin Zhang; Bing Zhang (Brain Imaging and Behavior, 2022)
Kidney and brain expressed protein (KIBRA) rs17070145 is associated with working memory function and cognitive processes. However, the neural mechanisms underlying these associations are not fully understood. This study aimed to explore the effect of KIBRA polymorphism on brain microstructure and blood oxygenation level dependent (BOLD) fluctuations using diffusion kurtosis imaging (DKI) and resting-state functional magnetic resonance imaging (fMRI) in 163 young adults. We also investigated that whether the imaging alterations mediated the association between KIBRA gene and working memory performance. Voxel-based analysis of DKI data showed that KIBRA C-allele carriers exhibited increased axial diffusivity (AD), radial diffusivity (RD) and mean diffusivity (MD) as well as decreased fractional anisotropy (FA), mean kurtosis (MK) and radial kurtosis (RK) compared with KIBRA TT homozygotes, primarily involving the prefrontal lobe, left precuneus and the left superior parietal white matter. Meanwhile, KIBRA C-allele carriers exhibited decreased amplitude of low-frequency fluctuation (ALFF) in the left precuneus compared to KIBRA TT homozygotes. Mediation analysis revealed that the DKI metrics (MK and RK) of the left precuneus mediated the effect of the KIBRA polymorphism on working memory performance. Moreover, the MK and RK in the left precuneus were positively correlated with ALFF in the same brain region. These findings suggest that abnormal DKI parameters may provide a gene-brain-behavior pathway in which KIBRA rs17070145 affects working memory by modulating brain microstructure in the left precuneus. This illustrates that DKI may provide additional biological information and reveal new insights into the neural mechanisms of the KIBRA polymorphism.

Failure mechanism of a slow-moving landslide on September 27, 2020, in Chang Nong Village, Guangxi, China - Jiaming Zhang; Zhi Zhou; Feng Lin; Qinggang Yang; Yi Luo (Landslides, 2021)

Research on the rainfall-induced regional slope failures along the Yangtze River of Anhui, China - Jiaming Zhang; Yi Luo; Zhi Zhou; Chikhotkin Victor; Modong Duan (Landslides, 2021)

A new pentacyclic triterpenoid from the leaves of Rhododendron dauricum L. with inhibition of NO production in LPS-induced RAW 264.7 cells - Jiaming Wang; Mei Jin; Chunshi Jin; Chao Ye; Yi Zhou; Rongshen Wang; Huanhuan Cui; Wei Zhou; Gao Li (Natural Product Research, 2020)

Large-Scale Test Model of the Progressive Deformation and Failure of Cracked Soil Slopes - Zhi Zhou; Jiaming Zhang; Fulong Ning; Yi Luo; Lily Chong; Kuangbiao Sun (Journal of Earth Science, 2020)

A new aryldihydronaphthalene-type lignan and other metabolites with potential anti-​inflammatory activities from Corispermum mongolicum Iljin - Yi Zhou; Mei Jin; Chunshi Jin; Chao Ye; Jiaming Wang; Jinfeng Sun; Cheng-Xi Wei; Wei Zhou; Gao Li (Natural Product Research, 2020)

Alleviation of atrazine toxicity to maize seedlings grown in soils with amendment of biochar derived from wheat under different temperatures - Yifan Wang; Yi Tang; Qun Jiang; Xinyuan Zhang; Weiling Xie; Ruizhen Li; Wenzhu Liu; Jiaming Kang; Ying Zhang (Environmental Science and Pollution Research, 2019)